Decolonizing the representations about colonization: geographic reflections - Neto, Jaime Bernardo (Geografares, 2020)
Most representations about the process of spatial expansion of capitalism over the spatial cuts that today constitute what we know as Brazil and Latin America, through the advance of colonization, perpetuates what some authors have been calling ideology of demographic voids, which would be the tendency to represent these spaces before their appropriation and incorporation into the capitalist world system as desert areas, without human beings, thus concealing the violence inherent in it. Despite the advances in Contemporary Social Theory, this type of timespace representation has still been reproduced and perpetuated in many historiographic and academic works from different areas of knowledge. The following article presents reflections on this phenomenon, developed with fulcrum in studies on the spatial profile that today constitutes the State of Espírito Santo, in order to understand the theoretical vices that corroborate the perpetuation of this type of representation.